The complete mitochondrial genome and phylogenetic analysis of the ocellated angelshark: Squatina tergocellatoides Chen, 1963. Issue 10 (3rd October 2022) - Jia, Chunbin; Shan, Binbin; Liu, Yan; Yang, Changping; Wang, Liangming; Sun, Dianrong
Abstract: The ocellated angelshark ( Squatina tergocellatoides Chen, 1963) is a threatened shark within the family Squatinidae. In the present study, we reported the mitochondrial genome sequence of the ocellated angelshark. The complete mitochondrial genome is 16, 683 bp in length and contains 37 mitochondrial genes and a control region as similar to most fishes. In addition, we constructed a maximum-likelihood phylogenetic tree of S. tergocellatoides and its relative species. This work will provide molecular data for further studies on S. tergocellatoides .